Legal Protection for Online Loan Business Actors Regarding personal data - Bonaventure Kevin Gunawan (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2023)
The purpose of this research is to find out whether the personal data protection law gives legal certainty to online loan business actors. The research method used is to use a normative approach and Law no. 27 of 2022 and the theory of legal certainty. From the research results of Law no. 27 of 2022 concerning Protection of Personal Data does not provide legal certainty for Online Loan business actors, Protection of Personal Data concerns online loan entrepreneurs to carry outannouncing data on its customers has increased, while an increase in online lending customers equals an increase in problems in billing stubborn creditors. Loan entrepreneurs certainly won't do billing by themselves and definitely need help from various sourcesoutsourcing which will spread the data of its customers, because many consumers will let go of responsibility and run away from the city or even the country.